Class 4 emphysematous pyelonephritis with emphysematous cystitis: a rare case report (BIRDEM Medical Journal, 2023)
Class 4 emphysematous pyelonephritis with emphysematous cystitis is an uncommon diagnosis. We report a case of class 4 emphysematous pyelonephritis with emphysematous cystitis, occurring in a young Bangladeshi diabetic lady, who presented with features of upper urinary tract infection and the diagnosis of emphysematous pyelonephritis was confirmed by computed tomography scan. She was treated conservatively.BIRDEM Med J 2023; 13(3): 160-162